Internal migration patterns to Fukushima following the nuclear accident based on vital statistics and the Fukushima health management survey - Tomoyuki Kobayashi; Masaharu Maeda; Naoko Horikoshi; Rie Mizuki; Maho Momoi; Tetsuya Ohira; Hirooki Yabe; Seiji Yasumura (BMC Public Health)
Abstract Background We examined the characteristics and mental health of people who migrated to the Fukushima Prefecture after the 2011 nuclear power plant accident through two studies. While the original community was disrupted by the nuclear accident, internal migrants from other prefectures in Japan have played an increasingly significant role in promoting the recovery process. Methods Study 1 used data from the Vital Statistics of Fukushima database from January 1999 to October 2023 to analyze shifts in migration patterns before and after the nuclear accident, focusing on the proportion of internal migrants who relocated to Fukushima following the accident. The dataset was based on the population census collected by the national government and changes in resident registration records, providing monthly population dynamics for all municipalities in the Fukushima Prefecture. Study 2 examined the mental health status of internal migrants using data from the Fukushima Health Management Survey, which has been conducted annually since 2011. A total of 4,139 participants were included in the study including individuals who registered as residents in the 13 municipalities designated as evacuation zones and migration recorded from the 2013 fiscal year onward. Results Study 1 showed that over 20% of the total population in the Fukushima Prefecture were internal migrants after the accident, and although the migration trends were originally declining, this trend was mitigated after the accident. The proportion of internal migrants from other prefectures in Japan was particularly high in Tomioka, Okuma, and Namie towns. Study 2 revealed that the mental health of the immigrants worsened year by year, with female internal migrants being more negatively affected in areas with a higher proportion of migrants. Conclusions This study highlights the increasing presence of internal migrants in Fukushima following the nuclear accident and the need for mental health care tailored to the immigrants specific challenges.